Colonialism, Race and Gender: A Multimodal Analysis of an Indonesian History Textbook - Utami, Indah Wahyu Puji (Jurnal Sejarah, 2021)
This study aims to unpack the complex representation of ideology and discourses of colonialism, race, and gender. Using social semiotic as a framework, this research investigates the meaning behind the text and images in an official history textbook published by the Indonesian Ministry of Education and Culture (MoEC). The images were counted and categorized before they were analyzed using multimodal discourse analysis. In term of visual design and the layout of the pages in the textbook, there is ample evidence that events and figures were depicted differently. This study also indicates a tendency of male domination in a history textbook, particularly the indigenous males. Meanwhile, the indigenous females were given a stage in the history textbook even though it is limited.